Body Composition and Digestive Enzyme Activity of Hard-Lipped Barb (Osteochilus vittatus) Feed with Supplementation of Spirulina platensis and Chlorella vulgaris - Simanjuntak, Sorta Basar Ida; Susilo, Untung; Syahputra, Havidh Ardika; Imelda, Imelda; Winasis, Siti (Molekul, 2025)
ABSTRACT. Cultivation of hard-lipped barb (Osteochilus vittatus) increased in the district of Banyumas, Indonesia. Supplementation Spirulina platensis and Chlorella vulgaris has lots utilized in field aquaculture as high nutritious food to increase fish production. Evaluation digestibility to S. platensis and C. vulgaris in hard-lipped barb fish can done with measurement composition body and activity enzyme digestion. The purpose of this study was to know the influence of supplementation of S. platensis and C. vulgaris and to find the most appropriate composition of supplementation to enhance body composition and digestive enzyme activity of hard-lipped barb. The study was conducted experimentally with completely randomized design (CRD) and consisting of five Treatments: P0 = without supplementation as control; P1 = S. platensis 6 g.kg-1; P2 = C. vulgaris 4 g.kg-1; P3 = ( S. platensis 3 g + C. vulgaris 2 g).kg-1; and P4 = ( S. platensis 2 g + C. vulgaris 3 g).kg-1, in four replicates. The results showed S. platensis and C. vulgaris increase hard-lipped barb protein, fat and fiber levels. C. vulgaris and combinations of S. platensis + C. vulgaris enhance activity trypsin-like, lipase, amylase, and alkaline phosphatase in foregut, hindgut, and hepatopancreas. C. vulgaris and S. platensis can be given as supplement of hard-lipped barb feed to enhance enzyme activity that contributing digestion​ to enhance body composition. Keywords: body composition, Chlorella vulgaris, enzyme, Osteochilus vittatus, Spirulina platensis